2011
DOI: 10.2527/jas.2009-2617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whole-crop pea (Pisum sativum L.) silages differing in condensed tannin content as a substitute for grass silage and soybean meal on the performance, metabolism, and carcass characteristics of lambs

Abstract: Two experiments were conducted to investigate the effect of inclusion of whole-crop pea (WCP) silages, differing in condensed tannin content, as a substitute for grass silage (GS) and soybean meal on lamb metabolism, performance, plasma metabolites, digestibility, and carcass characteristics. In both experiments lambs were offered either solely GS or a 50:50 mix on a DM basis of GS with either low-tannin (LTPS) or high-tannin (HTPS) pea silage ad libitum. Each forage mix was fed with either 400 g/d of low-prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In the current study, the diet DM digestibility was measured using AIA with an average of 0.81 kg kg -1 with no effect (p> 0.05) of additional tannin (Table 2). These results agree with the results reported by Hart et al (2012) who found that different tannin levels did not have a significant impact on DM digestibility when they fed lambs whole crop pea silage containing different levels of CT. Deaville et al (2010) also observed that there was no significant effect of supplementing 55.1 g of chestnut HT kg -1 DM to grass silage on DM and OM digestibility while an additional 55.6 g of mimosa CT kg -1 DM was found to reduce (p< 0.01) DM and OM digestibility. Makkar (2003) suggested that not all tannin protein complexes could dissociate in the abomasum, or complexes could be reversible in the small intestine depending on the tannin source, type, and concentration.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the diet DM digestibility was measured using AIA with an average of 0.81 kg kg -1 with no effect (p> 0.05) of additional tannin (Table 2). These results agree with the results reported by Hart et al (2012) who found that different tannin levels did not have a significant impact on DM digestibility when they fed lambs whole crop pea silage containing different levels of CT. Deaville et al (2010) also observed that there was no significant effect of supplementing 55.1 g of chestnut HT kg -1 DM to grass silage on DM and OM digestibility while an additional 55.6 g of mimosa CT kg -1 DM was found to reduce (p< 0.01) DM and OM digestibility. Makkar (2003) suggested that not all tannin protein complexes could dissociate in the abomasum, or complexes could be reversible in the small intestine depending on the tannin source, type, and concentration.…”
Section: Discussionsupporting
confidence: 92%
“…The results related to the lambs’ growth are not conclusive. Studies showed an increase [ 84 , 85 ], a decrease [ 86 , 87 ], or no effect [ 88 ] on the ADG of lambs.…”
Section: Polyphenolsmentioning
confidence: 99%
“…The authors declare no conflict of interest. [20] Brazil CL CT E Dey et al [106] India Ficus infectoria (n = 3) B, B, B N, N, N Abdalla et al [107] Brazil OP, Clep B, B N, N Fernandes et al [14] Brazil Mimosa tenuiflora (n = 3) B, B, B N, N, N Francisco et al [108] Portugal CL (n = 2) CT, CT N, N Girard et al [109] Switzerland LC and OV B, B N, N Guerreiro et al [110] Portugal CL (n = 4) CT, CT, CT, CT, CT N, N, N, N, N Gruffat et al [111] France OV (n = 2) CT, CT N, N Hart et al [112] United Kingdom Pisum sativum (n = 4) CT, CT, CT, CT, CT N, N, N, N, N Hassan et al [113] Egypt Punica granatum, MI, B B, B, B N, N, N Hatami et al [114] Iran Punica granatum (n = 3) B, B N, N Jerónimo et al [115] Portugal VV (n = 2), CL (n = 2) CT, CT, CT, CT, CT E, N, E, N Jerónimo et al [116] Portugal VV (n = 2), CL (n = 2) CT, CT, CT, CT, CT E, N, E, N Kamel et al [117] Saudi Arabia QU (n = 2) CT, CT E, E Kazemi and Mokhtarpour [118] Iran Prunus amygdalus (n = 3) B, B, B N, N, N Leparmarai et al [119] Switzerland VV B E Lima et al [120] Brazil Macrotyloma axillare B N Liu et al [21] China CH (n = 2) HT, HT E, E López-Andrés et al [91] Italy QU CT E Majewska and Kowalik [121] Poland VAC, Quercus sp. B, B N, N Flores et al [122] Brazil VV (n = 3) B, B, B N, N, N Flores et al [123] Brazil VV (n = 3) B, B, B N, N, N Moghaddam et al [124] Iran Berberis vulgaris (n = 2) B, B N, N Natalello et al [18] Italy Punica granatum B N Nobre et al [125] Brazil Psidium guajava (n = 4) B, B, B, B, B N, N, N, N, N Norouzian and Ghiasi [126] Iran Pistacia vera (n = 3) B, B, B N, N, N Obeidat et al [127] Jordan Ceratonia siliqua (n = 2) CT, CT N, N Odhaib et al [128] Malaysia RO (n = 3), NS (n = 3), B (n = 3) B (n = 9) N (n = 9) Pathak et al [13] India B, B CT, CT N, N Peng et al [95] Canada Dalea purpurea CT N Po et al…”
Section: Institutional Review Board Statement: Not Applicablementioning
confidence: 99%